Faktor-Faktor yang Mempengaruhi Knowledge Hiding pada Karyawan Hotel Bintang Lima di Bundaran HI - Geby Gracela Surnina Br Surbakti; Beta Oki Baliartati; Netania Emilisa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of factors affecting knowledge hiding among employees in five-star hotels in Bundaran HI using a quantitative approach with a survey method. The sample consists of 160 permanent employees selected through purposive sampling, with data collected via questionnaires and analyzed using Structural Equation Modeling (SEM). The results indicate that knowledge complexity and perceived supervisor support have a positive effect on psychological ownership and a negative effect on knowledge hiding. Psychological ownership also negatively affects knowledge hiding and is proven to mediate the relationship between knowledge complexity and perceived supervisor support on knowledge hiding. This study provides practical implications for hotel management in creating a work environment that supports open knowledge sharing and reduces knowledge hiding behavior among employees.